MODEL PENGEMBANGAN PERPUSTAKAAN DALAM MEMBUDAYAKAN MINAT BACA MAHASISWA - M S. Sumantri (Perspektif Ilmu Pendidikan, 2010)
Reading interest can be develop through planning, organizing, directing, and evaluating a program of creating and developing reading interest in the community as well as at school. This study attempted to develop reading interest of University Student at the State University of Jakarta, particularly at PGSD FIP UNJ. Creating a model of developing library to establish reading culture, this study applied the model to the student. At the end of the study it was found that the model is effective to develop students’ reading interest and habbit and also improve their learning achievement simultaneously.